Process communication in medical software development. Issue 3 (17th May 2013) - Polgár, Péter Balázs; Kazinci, Ferenc; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
ABSTRACT This paper describes a case study on using the Eclipse Process Framework in a medical software development organization to consolidate existing process descriptions. Although on nonmedical fields the Eclipse Process Framework was successfully used for process modeling and aiding process improvement efforts, the complex nature of the regulatory and process standard requirements on the medical software field needs special attention. In this environment, compliance to the regulatory is more important than improvement, so the process modeling has to implement these requirements in a very strict way, while supporting the business goals of the organization and enabling the improvement of the processes. Copyright © 2013 John Wiley & Sons, Ltd.